Origin and Evolution of the Multifaceted Adherens Junction Component Plekha7 - Kourtidis, Antonis; Dighera, Bryan; Risner, Alyssa; Hackemack, Rob; Nikolaidis, Nikolas (Frontiers in Cell and Developmental Biology, 2022)
Plekha7 is a key adherens junction component involved in numerous functions in mammalian cells. Plekha7 is the most studied member of the PLEKHA protein family, which includes eight members with diverse functions. However, the evolutionary history of Plekha7 remains unexplored. Here, we outline the phylogeny and identify the origins of this gene and its paralogs. We show that Plekha7, together with Plekha4, Plekha5, and Plekha6, belong to a subfamily that we name PLEKHA4/5/6/7. This subfamily is distinct from the other Plekha proteins, which form two additional separate subfamilies, namely PLEKHA1/2 and PLEKHA3/8. Sequence, phylogenetic, exon-intron organization, and syntenic analyses reveal that the PLEKHA4/5/6/7 subfamily is represented by a single gene in invertebrates, which remained single in the last common ancestor of all chordates and underwent gene duplications distinctly in jawless and jawed vertebrates. In the latter species, a first round of gene duplications gave rise to the Plekha4/7 and Plekha5/6 pairs and a second round to the four extant members of the subfamily. These observations are consistent with the 1R/2R hypothesis of vertebrate genome evolution. Plekha7 and Plekha5 also exist in two copies in ray-finned fishes, due to the Teleostei-specific whole genome duplication. Similarities between the vertebrate Plekha4/5/6/7 members and non-chordate sequences are restricted to their N-terminal PH domains, whereas similarities across the remaining protein molecule are only sporadically found among few invertebrate species and are limited to the coiled-coil and extreme C-terminal ends. The vertebrate Plekha4/5/6/7 proteins contain extensive intrinsically disordered domains, which are topologically and structurally conserved in all chordates, but not in non-chordate invertebrates. In summary, our study sheds light on the origins and evolution of Plekha7 and the PLEKHA4/5/6/7 subfamily and unveils new critical information suitable for future functional studies of this still understudied group of proteins.